Computational Intelligence in Data Science 6th IFIP TC 12 International Conference, ICCIDS 2023, Chennai, India, February 23-25, 2023, Revised Selected Papers - Chandran K R, Sarath; N, Sujaudeen; A, Beulah; Hamead H, Shahul (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book constitutes the proceedings of the 6th IFIP TC 12 International Conference on Computational Intelligence in Data Science, ICCIDS 2023, which took place in Kalavakkam, India, in February 2023. The 24 full papers presented in this volume were carefully reviewed and selected from 134 submissions. The major theme of the conference was intended to be computation intelligence and knowledge management. Various emerging areas like IoT, cyber security and data science need computation intelligence to align with the cutting-edge research. Machine learning delivers insights hidden in data for rapid, automated responses and improved decision making. Machine learning for IoT can be used to project future trends, detect anomalies, and augment intelligence by ingesting image, video, and audio.
Smart Driving Alert System using MT CNN -- Expert System for Real Time Arm Movement Recognition based on Surface EMG Signal -- Edge Detection and Huffman Encoding based Image Steganography with High Data Embedding Capacity -- DAPP IT - Multipurpose ID Card System for Universities -- Local Vegetable Freshness Classification Based on Chronological Monitoring using Transfer Learning Approach -- Analysis of Cost-Sensitive Algorithms for Degree of Imbalancing -- Secure Image Encryption Model for Cloud-based Healthcare Storage using Hyperchaos and DNA encoding -- A Comprehensive Study on Feature Extraction Techniques for Indian Sign Language Recognition System -- FinTech: Deep Learning-based Sentiment Classification of User Reviews from Various Bangladeshi Mobile Financial Services -- The Use of The Semantic Network for Categorization of Problems Solved by Design Thinking -- Cloud Based Remote File Access from PC to Mobile Using File Directory -- Stock Trade Recommendations using Knowledge Graph -- Understanding the Determinants of Adoption of Healthcare Information Technology -- Static Clustering Centralized Multi-Hop Routing Protocol Based on Fuzzy Logic with Fish Swarm Intelligence -- Computer vision aided machine learning framework for detection and analysis of arm flapping stereotypic behavior exhibited by the autistic child -- Social Media Hate Speech Detection Using Machine Learning Approach -- Frontotemporal Dementia Detection Model based on Explainable Machine Learning Approach -- AJNA - Voice Assisted Captioning Tool for the Blind -- Extraction of Vocal Tract Length from Formant Frequencies for Forensic Speech Applications in Noisy Environment -- Smart Parking System with Automated Vehicle Log using Haar cascade classifier ANPR -- Gradient Boosting-Based Predictive Click Fraud Detection using Manifold Criterion Variable Elimination -- Cataract Fundus Image Detection using Hybrid Deep Learning Model -- Enhanced Image Caption Generator Using Deep Learning.
Keywords: Data mining; Application software; Artificial intelligence; Image processing -- Digital techniques; Computer vision; Computers; Data Mining and Knowledge Discovery; Computer and Information Systems Applications; Artificial Intelligence; Computer Imaging, Vision, Pattern Recognition and Graphics; Computing Milieux